Microwave-assisted freeze drying of pineapple: Kinetic, product quality, and energy consumption. (January 2023) - Chen, Bo-Lin; Lin, Guan-Syun; Amani, Mohammad; Yan, Wei-Mon
Abstract: Among the advanced drying methods, vacuum freeze-drying (VFD) preserves the quality of food to the greatest extent, but its biggest disadvantage is its high energy consumption. The microwave-assisted freeze drying is expected to greatly reduce the energy consumption of drying process compared to VFD. In this paper, firstly, the eutectic temperature analysis of the pineapple slices is performed using resistance method and the eutectic point of −15 °C is obtained. Secondly, the impacts of four design variables including transition moisture content, microwave power density, drying temperature, and rotational speed of turntable on the product quality and energy consumption are deeply evaluated and discussed. The results show that the higher the microwave power density, the faster the drying rate. For example, the drying process reaching the final moisture content completes in 30, 60, and 90 min under power density of 8, 6, and 4 W/g, respectively. It is observed that employing a rotating turntable and a temperature control system leads to the uniform heating of the material and improved quality of products. Moreover, the lower the transition moisture content, the better the quality of dried products. In order to maintain the appearance of the product, the transition moisture content during the drying process should be within the range of 10–30%. Finally, Taguchi method is used to analyze the trend of experimental optimization. It is found that the most obvious factor affecting the comprehensive score of microwave-assisted freeze-drying process is transition moisture content, followed by the drying temperature and rotational speed. The least affecting parameter is the microwave power density. It is concluded that the microwave-assisted freeze-drying process under the transition moisture content of 20%, drying temperature of 40 °C, turntable rotational speed of 8 rpm, and microwave power density of 6 W/g has the efficient drying performance, saving 34.5% energy consumption and 33.3% drying time compared to pure VFD.